The Effect of Inflation and Interest Rates on Rupiah Exchange Rate Volatility in Indonesia (2023-2024) - Rahmawati, Nur Syarifah; Afriza, Reyhan Dzaki Hafidz; Yuniasih, Rita; Anggraini, Sovita Ayu; Muflihin, Mohammad Dliyaul (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2026)
This study aims to analyze the effect of inflation and interest rates on rupiah exchange rate fluctuations during the period January 2023–December 2024. The study uses a quantitative approach with multiple linear regression methods on monthly data sourced from the Central Statistics Agency and Bank Indonesia. The independent variables include inflation and interest rates (BI 7-Day Reverse Repo Rate), while the dependent variable is the fluctuation of the rupiah exchange rate against the US dollar. The results show that, both partially and simultaneously, inflation and interest rates do not have a significant effect on the fluctuation of the rupiah exchange rate. This finding indicates that exchange rate dynamics during the study period were more influenced by external pressures than by domestic macroeconomic factors. The scientific contribution of this research lies in presenting the latest empirical evidence on the weakening effectiveness of domestic monetary policy transmission on exchange rate volatility in the context of global monetary tightening. Theoretically, these results confirm that the interest rate parity approach and monetary framework are not always able to explain short-term exchange rate fluctuations when external factors are dominant. The implication is that foreign exchange risk management needs to strengthen hedging strategies, businesses must anticipate potential increases in import costs due to exchange rate volatility, and pricing decisions need to consider exchange rate uncertainty as a strategic factor that is not fully responsive to domestic interest rate policy.